Crops, Shifted Center and Its Ecological Effect in Central Maluku - Kadir, Hatib (IAIN Ambon, 2021)
This article describes the history of Ambon city and island which became the center of political power and trade and its correlation with landscape and geographical conditions as well as population mobility in the 17th century. In addition, the spice plants succeeded in creating inter-island relations and attracting workers from outside Maluku to stay and settle down. At the end of this paper, the change in the political and economic center has created various changes in the ecology and landscape of the city and Ambon Island until the 20th century. This paper is resulted from archival research conducted from 2015-2017 from various libraries in Ambon City, especially the Rumphius Library and the Maluku Cultural Values Preservation Center.Keywords: History of the City, Ambon Island, Center of Political Power and Trade